THE DEVELOPMENT OF APPLIED LINGUISTICS: HISTORICAL, THEORETICAL AND PRACTICAL PERSPECTIVES (Ustozlar uchun, 2025)
This article explores the development of Applied Linguistics as an interdisciplinary field that bridges linguistic theory and real-world language-related problems. The study examines the historical evolution of Applied Linguistics, its theoretical foundations, and its practical applications in areas such as language teaching, translation, discourse analysis, and sociolinguistics. Particular attention is given to how Applied Linguistics has evolved in response to globalization, technological advancement, and educational reform. The article highlights the role of Applied Linguistics in enhancing communication, promoting language policy, and addressing contemporary linguistic challenges in multicultural societies.